Production of starch nanoparticles by electrospraying as a delivery system for Vanillin [Nişasta nano parçaciklarin elektro pöskörtm eyöntemi ile vanilya ta?iyici olarak öretilmesi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
In recent years, polysaccharide biopolymers have attracted great interest due to being more hydrophilic and nontoxic in comparison with synthetic polymers. It's a new candidate for being substitute synthetic polymers owing to its biocompatible, renewable and biodegradable properties. The most abundant and inexpensive natural polysaccharide biopolymer starch is found in plant tissues and produced by mostly higher order plants as a means of storing energy. In this study, starch was developed as a nanoparticles by Electrospraying method. We optimized electrospraying parameters such as voltage (15-25 kV), flow rate (1-4 ml/h) and concentration of starch solution (%3.3-%16) for producing, uniform, monodispersity and pure starch nanoparticle. Vanillin, is a food additive, a fascinating substance that creates perception with the smell in the food industry. It's production is quite costly. Like pudding, cream, ice-cream, angel-cake, cookies, chocolate, and beverages commercial foods require to use vanilla. Since Electrospraying is a novel alternative microencapsulation technique which can generate very fine particulate structures in a one-step process, vanillin was sprayed-coated by starch nanoparticles. So, vanillin flavor sensory quality will be enhanced by releasing vanillin by the amylase enzyme that found in saliva. In addition, the loading of vanilla is done at different rates to make it commercially easy available and optional for price flexibility. © 2017 IEEE.
Keywords: Electrospraying; Nanoparticle; Starch; Vanillin